Design and development of pyrolysis system to produce wood vinegar - Iberahim, Suzilawati (2013)
Air pollution such as haze often occur due to the open burning of agricultural waste. In order to counter the problem this research existed with the target to turn agricultural waste to high quality product and reusable. Since this research located at the northern region of Malaysia, the most popular agricultural waste are paddy husk and paddy straw. Open burning normally happen after the harvesting season either by the farmers or paddy factory owners. Pyrolysis system is built to counter the problem by turning smoke from the agricultural waste to another product called ‘liquid oil’. Liquid oil is analysed with 13 chemical compositions such as Acetic Acid, Ethanol, Furfural and etc. Content percentage for Carbon, Nitrogen, Oxygen, Hydrogen and Sulphur in the liquid oil produced is nearly the same with the previous research. Results shows that liquid oil produced from the paddy husk smoke condensation process can also form wood vinegar. Wood vinegar is a type of liquid oil used by the industry as growth catalyze, disease control agent for plant and etc. Other than controlling the air pollution from open burning, liquid oil also beneficial to the farmers as it can replace the use of chemical fertilizer. As publicly known chemical fertilizer can cause the soil to be acidic and leads to another problem which is water pollution